Risk of acute pancreatitis with incretin-based therapy: a systematic review and updated meta-analysis of cardiovascular outcomes trials. Issue 4 (2nd April 2020) - Singh, Awadhesh Kumar; Gangopadhyay, Kalyan Kumar; Singh, Ritu
ABSTRACT: Background: The link of acute pancreatitis (AP) with Incretin based therapies (IBTs) in type 2 diabetes has existed since United States Food and Drug Administration alert in 2010. This issue still remains unresolved due to conflicting results among studies. Research design and methods: We performed a systematic search of the PubMed, Embase, and Cochrane Library databases until 31 July 2019, and retrieved all cardiovascular outcome trials (CVOTs) of IBTs conducted for ≥12 months that reported the pre-specified and or pre-adjudicated pancreatitis outcomes. Subsequently, we conducted a meta-analysis to study the risk of AP observed with IBT in CVOTs. Results: A meta-analysis of seven CVOTs of GLP-1 receptor agonists (GLP-1RAs) compared with placebo (N = 55, 932) found no significant increase in AP (odds ratio [OR], 1.05; 95% confidence interval [CI], 0.77–1.42; p = 0.77). In contrast, meta-analysis of five CVOTs comparing DPP-4 inhibitors with placebo (N = 47, 714) and six CVOTs comparing DPP-4 inhibitors with placebo or active comparator (N = 53, 747), found a significant increase (OR, 1.81; 95% CI, 1.21–2.70; p = 0.04 and OR, 1.54; 95% CI, 1.08–2.18; p = 0.02, respectively) in AP without any significant heterogeneity. Conclusions: This meta-analysis revealed a significant association between pancreatitis and DPP-4 inhibitors; however, no such association was observed for GLP-1RAs.